Morphological diversity of populations of the genus Prosopis in the semiarid Chaco of northern Cordoba and southern Santiago Del Estero - Joseau, Marisa Jacqueline; Verga, Anibal; Díaz, María del Pilar; Julio, Norma Beatríz (Scientific Research, 2018)
The objective of this study consisted in the characterization of morphological variability presented in the Prosopis population in the corridor that unites the semiarid with the arid region in Argentina. In this region, four species of Prosopis get in contact (P. chilensis, P. flexuosa, P. alba and P. nigra). Due to the fact that these species make fertile hybrids, this corridor has an enormous diversity. The mother’s allowed the differentiation of five morphologic groups, which from the point of view of classic taxonomy have been classified in 16 taxa. Only groups 3 and 4 presented intermediate characteristics. The morphologic study of the descendants showed that the regrouping of the intermediate groups had a high error rate. This fact reaffirms the condition of intermediate groups. The canonical correlation analysis between the morphologic variables of the mothers and the seedlings revealed that each morphologic group had its own association of canonical variables between mothers and their seedlings, and that the variability observed in the set of the mothers and their seedlings follows a certain order. The enormous existing morphologic diversity in the Prosopis populations of the semi-arid Chaco of the north of Córdoba and southeast of Santiago del Estero was ordered in five morphologic groups. The descendant’s morphologic studies confirmed the existence of the defined morphologic-genetic groups.